Social integration of migrants from Ukraine and Belarus in Lithuania - Skučienė, Daiva; Poškus, Žygimantas; Kazakevičiūtė, Beatričė (Socialinė teorija, empirija, politika ir praktika, 2023)
The phenomena of migration in today’s society is not surprising, but how often do we think about immigrants and their interactions with the local population, within themes of language, culture, social life, employment and general integration. International organizations say that although basic rights and protection of immigrants is ensured in Lithuania, immigrants in our country still do not have the opportunity to participate in public life as well as they should. The aim of this article is to refresh our knowledge of migrants' own experiences with regards to social integration and their own subjective welfare, by specifically examining the two largest groups of immigrants, Ukrainians and Belarusians. For the purpose of the study, 20 semi-structured interviews were conducted, of which 10 were with Ukrainians and 10 with Belarusians. The study revealed that language is an important factor in the formation of a new identity and social integration. It was also noted that immigrants from Ukraine and Belarus have varying degrees of success entering the local labor market and they usually have to work in lower-skilled jobs. It is also worth mentioning that immigrants support their immigration efforts by way of similar culture and adaptation in their national communities, churches or social networks. Lastly, immigrants from Ukraine and Belarus are satisfied with life in Lithuania and notice positive differences compared to their country of origin, such as transparency and order in the country, a well-functioning banking and public transport system. They also note that the mentality of local Lithuanians and their own is similar, which is a development that has happened due to a shared Soviet experience and proficiency in the Russian language.
Keywords: immigration; social integration; subjective well-being; labour marker